Penerapan Restorative Justice terhadap Anak yang Berkonflik dengan Hukum dalam Prespektif The Best Interest of The Child : Studi Komparatif KUHP Nasional 2023 dan Undang-Undang Sistem Peradilan Pidana Anak serta Analisis Putusan Pengadilan Negeri Kupang Nomor 10/PID.SUS-ANAK/2024 - Maria Fantricia S. Pama; Simplexsius Asa; Juliana Susantje Ndolu (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
The application of Restorative justice to children in conflict with the law in criminal justice practice continues to raise issues and debates, particularly regarding the alignment between normative frameworks and their implementation from the perspective of the best interest of the child. This condition is influenced by the persistent dominance of a conventional punitive paradigm, despite the normative shift toward a more humanistic and restorative approach. This research is a normative legal study examining legal norms contained in legislation, court decisions, and relevant legal doctrines, using statutory, conceptual, and case approaches. The results show that: (1) The formulation of Restorative justice in the Indonesian Criminal Code 2023 reflects a paradigm shift toward a more humanistic and restorative approach, in line with the principle of the best interest of the child. However, the regulation remains general and lacks operational clarity, potentially leading to inconsistencies in its application; (2) The application of Restorative justice in the Kupang District Court Decision Number 10/Pid.Sus-Anak/2024 does not substantively reflect the principle of the best interest of the child, as judicial considerations remain oriented toward punishment, while aspects of recovery and the child’s future protection have not been prioritized.